Flammable societies : studies on the socio-economics of oil and gas - McNeish, John-Andrew; Logan, Owen, 1963- (Pluto Press, 2012)
The impact of the oil and gas industry - paradoxically seen both as a blessing and a curse on socio-economic development - is a question at the heart of the comparative studies in this volume stretching from Northern Europe to the Caucasus, the Gulf of Guinea to Latin America. Britain's transformation under Margaret Thatcher into a supposedly post-industrial society orientated towards consumer sovereignty was paid for with revenues from the North Sea oil industry, an industry conveniently out of sight and out of mind for many. Drawing on bottom-up research and theoretical reflection the authors question the political and scientific basis of current international policy that aims to address the problem of resource management through standard Western models of economic governance, institution building and national sovereignty. This book offers valuable material for students and researchers concerned with politics, inequality and poverty in resource-rich countries. Among the key critical issues the book highlights is the need to understand the politics of social territorialism as a response to exclusionary geopolitics.